Leveraging Talent for a Sustainable Future: A Multidisciplinary Examination of Public Sector Talent Management Strategies - Kurniawan, Agus; Wijoyo, Suparto (RSF Conference Series: Business, Management and Social Sciences, 2024)
High-performing individuals are crucial for organizational success. This study examines talent management in the Indonesian public sector, revealing a significant gap between the competency needs of organizations and the availability of suitable talent. Key challenges include the difficulty of recruiting and retaining highly qualified personnel due to budgetary constraints and uncompetitive compensation policies compared to the private sector. Additionally, career development is hindered by a lack of leadership commitment and inadequate follow-up on assessment outcomes. This research explores the challenges and opportunities in implementing public sector talent management and formulating effective strategies. The methodology employed is a Systematic Literature Review (SLR) involving identifying, evaluating, and interpreting literature from various research reports and scholarly journals. The findings underscore the critical role of innovative and labour market-responsive talent management practices in enhancing organizational performance. The primary challenges lie in the misalignment of talent management policies with public sector needs and resource and policy support limitations. In conclusion, the public sector must cultivate tailored talent management strategies aligned with the local context and advocate for more flexible policies to optimize organizational performance. These insights are intended to guide policymakers and practitioners in improving talent management effectiveness in Indonesia's public sector.